Juan Bernal Ponce: life goes on - Alvarado Venegas, Ileana (2019)
This article shows a review of the life of the Chilean artist Juan Bernal Ponce, exiled in Costa Rica as a result of the 1973 putsch. He also reflects on his work, based on the exhibition Encounter with the tropic and other directions in exile, made at the Embassy of Chile in Costa Rica in September 2018. A Chilean who knew, even with a broken heart, to rebuild his life and enjoy it. Recived: 06-04-2019 Approved: 06-14-2019